The Political Language of Disaster: Indonesian Government Communication for Handling the Covid-19 Pandemic - Fariz Alnizar; Fadlil Munawwar Manshur (Faculty of Social and Political Sciences, Universitas Gadjah Mada, 2022)
Indonesia is one of the most populous countries exposed to Covid-19 with a high mortality rate. The pandemic has been in Indonesia since March 2020, but before the Covid-19 virus was officially declared to enter Indonesia, the Indonesian government previously took this threat lightly. It showed that the Indonesian government was using political language such as disaster communication. Some disparaging comments left public officials. This research uses a qualitative approach with content analysis techniques. The primary data is derived from President Joko Widodo’s speech at Bogor Palace and the tweets of @kemenkes @BNPB and @Jokowi’s Twitter accounts related to Covid-19. This research examines how the Indonesian government communicates its policies in overcoming the Covid-19 pandemic. Furthermore, this research is intended to reveal the narrative developed by the Indonesian government in campaigning for policies to overcome the Covid-19 pandemic. The results show that there are doubts from the government in determining the policies to be taken to overcome the spread of Covid-19. The narrative developed by the government—like the phrase “new normal” and “enggak mudik” phrase—is a narrative that is intended to create calm, even though it can endanger public health.